LOCAL COMMUNITIES AND THE PROCESS OF LOCAL ECONOMIC DEVELOPMENT - CONSTANTIN BRAGARU (Challenges of the Knowledge Society)
The present paper focuses on sustainable development and the specific objectives that Romania intends to achieve in order to reach a new model of development that is capable of generating high value added, is interested in knowledge and innovation, and aims to improve the quality of life in harmony with the natural environment. The paper also analyzes the process of local development that Romania started in 2000 with the financial support of United Nations Development Programme - “Romania within the framework of Local Agenda 21” and continued within Regional Operational Programme 2007-2013. Finally, the study reveals the regional and local development priorities established by Romania within “The National Sustainable Development Strategy” for the next period of time – 2013-2020 -2030.